2012
DOI: 10.1097/ccm.0b013e318260cc33
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics in the critically ill

Abstract: Probiotics appear to reduce infectious complications including ventilator-associated pneumonia and may influence intensive care unit mortality. However, clinical and statistical heterogeneity and imprecise estimates preclude strong clinical recommendations. Further research on probiotics in the critically ill is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
52
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 119 publications
(59 citation statements)
references
References 92 publications
4
52
1
2
Order By: Relevance
“…The main findings of our review were in agreement with the recent previous meta-analyses by Siempos 2010 and Petrof 2012, but contradict the results of another meta-analysis on the same topic (Gu 2012). The meta-analysis by Siempos 2010 included five studies with a total of 689 participants.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The main findings of our review were in agreement with the recent previous meta-analyses by Siempos 2010 and Petrof 2012, but contradict the results of another meta-analysis on the same topic (Gu 2012). The meta-analysis by Siempos 2010 included five studies with a total of 689 participants.…”
Section: Discussionsupporting
confidence: 75%
“…Their results showed that probiotics appeared to be associated with a lower incidence of VAP. The meta-analysis by Petrof 2012 included 23 studies with a total of 2153 participants and indicated, again, that lower VAP incidence was associated with people receiving probiotics. The meta-analysis by Gu 2012 included seven studies with a total of 1142 participants and indicated that probiotics show no benefit in VAP prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…However, when exclusively higher-quality trials were pooled, the favorable outcomes disappeared. Contrariwise, the beneficial effects were obvious in trials with an inherent high risk of bias [8]. In the same line, the present study by Zeng et al seems to be yet another non-blinded trial reporting tight statistical significance (p = 0.03).…”
supporting
confidence: 73%
“…This study adds to the existing literature summarized in a meta-analysis that demonstrated an overall reduction in infectious complications and VAP [8]. However, when exclusively higher-quality trials were pooled, the favorable outcomes disappeared.…”
mentioning
confidence: 51%
See 1 more Smart Citation